Consumption and market share of cholesterol-lowering drugs in high-risk patients before and after the release of the 2013 ACC/AHA cholesterol guidelines: a retrospective observational study - Tzu-Tsen Kuo; Yaw-Bin Huang; Ching-Jung Hsieh (BMJ Open)
Objective We examined the use of cholesterol-lowering drugs in Taiwan in high-risk patients before and after the release of the 2013 American College of Cardiology and the American Heart Association (ACC/AHA) cholesterol guidelines.Design Retrospective observational study.Setting Kaohsiung Chang Gung Memorial Hospital database, Kaohsiung City, Taiwan.Participants Outpatients aged ≥20 years with atherosclerosis cardiovascular disease, familial hypercholesterolaemia and diabetes.Primary and secondary outcome measures Data on brand and generic names, use and dosage of cholesterol-lowering drugs in 2012 and 2015 were compiled and the total amount used was calculated. Differences in usage and market share were compared. Usage rates of single and fixed-dose combination (FDC) products were compared.Results The number of patients receiving ambulatory care increased from 36 367 in 2012 to 41 807 in 2015. Single (3 679 979–4 568 086 tablets) and FDC (540 522–572 954 tablets) product use increased from 2012 to 2015, respectively. Statins were the most commonly prescribed medications in 2012 (71.14%) and 2015 (72.91%). The average monthly consumption of statin among high-risk patients in 2012 was 269 948.8 tablets, and it increased significantly to 343 975.3 tablets in 2015. The average monthly consumption of pitavastatin was 34 113.4 tablets in 2015, which was significantly higher than 0 in 2012. Conversely, the highest decline was observed for fluvastatin use, with the average monthly consumption being 38 754.3 tablets in 2015, which was significantly lower than 45 929.8 tablets consumed in 2012. Regarding FDC therapy for cholesterol-lowering drugs, Vytorin (ezetimibe 10 mg + simvastatin 20 mg) use was the highest among all FDCs in 2015.Conclusions The 2013 ACC/AHA cholesterol guidelines likely promoted the use of fixed-dose, high-intensity and moderate-intensity monotherapy and FDC therapy statins in high-risk groups, and this was consistent with the use of high-intensity or moderate-intensity statins in the present study. Furthermore, these changes were associated with increased effectiveness and reduced adverse effects.